Campaign studies for investigating the coupling processes in the thermosphere and ionosphere - Borries, Claudia; Sato, Hiroatsu; Günzkofer, Florian Ludwig; Yaroshenko, Victoriya; Pokhotelov, Dimitry (2022)
The thermosphere and ionosphere (TI) system, which represent neutral and charged particles respectively in the upper atmosphere in more than 80 km altitude, is characterized by highly variable electrodynamic processes. Changes in the thermosphere find their response in the ionosphere and vice versa. The TI system is driven to a large extend by forcing from the Sun causing a typical daily, seasonal, 11-year and other regional variability. Solar forcing also includes storm conditions, when suddenly large amounts of solar wind energy is transferred into the TI system, resulting in significant changes in thermosphere and ionosphere conditions. Although the solar forcing dominates the TI variability, the dynamics and chemistry from the atmosphere below do not have a neglectable influence, too. In this presentation, I will show campaign studies with the EISCAT instrumentation in North-Norway, which reveal solar and atmosphere TI-coupling processes on different temporal and spatial scales. The observations are combined with modelling results from numerical models of the TI system.